VERBA EMOTIF BAHASA MELAYU DIALEK KETAPANG KAJIAN SEMANTIK - Muhammad Setiawan; Amriani Amir; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe Dialect of Ketapang Malay is one of the regional languages in West Kalimantan, precisely in Matan Hilir Subdistrict, Ketapang District. BMDK is used to communicate in daily life and in official events, in which it is used in traditional cases, traditional ceremonies, and preservation of regional culture in the form of poetry, rhymes, folklore, and songs. This research is related to   linguistics. This research is focused on the semantic field about emotive verbs, which is one of the other verbs. In general the problem in this study is "The emotive verbs", and the particular problem is the clarification of the inventory of emotive verbs and the meaning of emotive verbs in Bahasa Melayu Dialek Ketapang or simplify as BMDK. The method used in this research is descriptive method. The data in this study are words that contain emotive BMDK verbs that are used by the Malay community of Ketapang, Kelurahan Tengah Matan Hilir Selatan, Delta Pawan District. The data source in this study is the BMDK which was spoken directly by the informant. Data collection techniques are skilled engaging and interview techniques. Data collection tools used were instruments in the form of questions, pictures, photos and data cards.Based on the results of the data analysis in Chapter IV of the researchers on various problems discussed in this study, it was concluded that BMDK's emotive verbs contained 39 of emotive verbs.Keywords: Emotive Verbs , Ketapang Malay Dialect.